When holding your horses meets the deer in the headlights: time-frequency characteristics of global and selective stopping under conditions of proactive and reactive control - Lavallee, Christina F.; Meemken, Marie T.; Herrmann, Christoph S.; Huster, Rene J. (Frontiers in Human Neuroscience, 2014)
The ability to inhibit unwanted thoughts or actions is crucial for successful functioning in daily life; however, this ability is often impaired in a number of psychiatric disorders. Despite the relevance of inhibition in everyday situations, current models of inhibition are rather simplistic and provide little generalizability especially in the face of clinical disorders. Thus, given the importance of inhibition for proper cognitive functioning, the need for a paradigm, which incorporates factors that will subsequently improve the current model for understanding inhibition, is of high demand. A popular paradigm used to assess motor inhibition, the stop-signal paradigm, can be modified to further advance the current conceptual model of inhibitory control and thus provide a basis for better understanding different facets of inhibition. Namely, in this study, we have developed a novel version of the stop-signal task to assess how preparation (that is, whether reactive or proactive) and selectivity of the stopping behavior effect well-known time-frequency characteristics associated with successful inhibition and concomitant behavioral measures. With this innovative paradigm, we demonstrate that the selective nature of the stopping task modulates theta and motoric beta activity and we further provide the first account of delta activity as an electrophysiological feature sensitive to both manipulations of selectivity and preparatory control.